Financial consulting: A qualitative study on its role in financial decision making - Julia Sprenger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
The current study examines the way people deal with financial decisions. The purpose of this study is to explore the role of financial consulting in the decision making process and the complex decision dynamics in the run up to a decision. Data for this study were collected through a series of semi-structured interviews with both financial consultants of a savings bank and their clients. The findings provide insights into different attitudes towards financial decision making, locate financial consulting within the decision process, and compare the information habits and the degree to which decision autonomy is maintained, restricted, or given up across different types of clients. Besides, the study shows how trust between client and consultant encourages reciprocal behavior and increases the willingness to accept opportunity costs. The paper discusses these findings with respect to consulting practices and consumer policy and outlines directions for future research. – – Diese Studie untersucht die Art und Weise wie Menschen mit finanziellen Entscheidungen umgehen. Ziel der Studie ist es, die Rolle von Finanzberatung im Entscheidungsprozess und die komplexen Dynamiken im Vorfeld einer Finanzentscheidung zu untersuchen. Die Daten für diese Studie wurden in einer Reihe semi-strukturierter Interviews mit Finanzberatern einer Sparkasse und ihren Kunden gesammelt. Die Ergebnisse geben einen Einblick in verschiedene Einstellungen zum Thema Finanzentscheidungen, verorten Finanzberatung innerhalb des Entscheidungsprozesses und vergleichen die Informationsgewohnheiten verschiedener Kundentypen sowie den Grad, zu dem Entscheidungsautonomie von ihnen aufrechterhalten, beschränkt oder aufgegeben wird. Daneben zeigt die Studie, wie Vertrauen zwischen Kunde und Berater reziprokes Verhalten fördert und die Bereitschaft erhöht, Opportunitätskosten zu akzeptieren. Das Papier diskutiert die Ergebnisse im Hinblick auf Beratungspraktiken und Verbraucherpolitik und umreisst Ideen für zukünftige Forschung.
Keywords: D14; D18; D83; G21; 330; financial decision making; financial consulting; interviews; decision autonomy; information